Comparative investigation of the cleavage step in the synthesis of model peptide resins: Implications for N-alpha-9-fluorenylmethyloxycarbonyl-solid phase peptide synthesis - Jubilut, Guita Nicolaewsky; Cilli, Eduardo Maffud [UNESP]; Crusca, Edson; Silva, Elias Horacio; Okada, Yoshio; Nakaie, Clovis Ryuichi (Pharmaceutical Soc Japan, 2007)
Based on our studies of the stability of model peptide-resin linkage in acid media, we previously proposed a rule for resin selection and a final cleavage protocol applicable to the N-alpha-tert-butyloxycarbonyl (Boc)-peptide synthesis strategy. We found that incorrect choices resulted in decreases in the final synthesis yield, which is highly dependent on the peptide sequence, of as high as 30%. The present paper continues along this line of research but examines the N-alpha-9-fluorenylmethyloxycarbonyl (Fmoc)-synthesis strategy. The vasoactive peptide angiotensin II (All, DRVYIHPF) and its [Gly(8)]-All analogue were selected as model peptide resins. Variations in parameters such as the type of spacer group (linker) between the peptide backbone and the resin, as well as in the final acid cleavage protocol, were evaluated. The same methodology employed for the Boc strategy was used in order to establish rules for selection of the most appropriate linker-resin conjugate or of the peptide cleavage method, depending on the sequence to be assembled. The results obtained after treatment with four cleavage solutions and with four types of linker groups indicate that, irrespective of the circumstance, it is not possible to achieve complete removal of the peptide chains from the resin. Moreover, the Phe-attaching peptide at the C-terminal yielded far less cleavage (50-60%.) than that observed with the Gly-bearing sequences at the same position (70-90%). Lastly, the fastest cleavage occurred with reagent K acid treatment and when the peptide was attached to the Wang resin.
Keywords: peptide synthesis; peptidyl resin; cleavage; linker group